Systematic bias in trait attributions for deceased friends and relatives - Galang, Adrianne John R. (Animo Repository, 2017)
© 2017 Elsevier Ltd Bering (2006) put forward the claim that the deceased are viewed as authoritative moral figures, and Bering, MacLeod, and Shackelford (2005) present evidence supporting this. We extend Bering's conjecture through a within-subjects quasi-experimental study testing the possibility that person perception regarding personality traits might shift in a context where (a) the target is someone known personally, and (b) the target happens to be deceased. One-hundred ten undergraduate students in Manila were asked to rate the Big Five traits of two older adult individuals known to them personally, one of whom must be alive, and the other deceased. Using multilevel modeling, we found that decedent targets on average were rated with higher Extraversion and Agreeableness scores compared to living targets, and that this held even when controlling for relational closeness and other possible covariates. Additionally, relational closeness was associated with higher ratings for all traits regardless of whether they were alive or not, indicating the possibility of a halo effect.